The contribution of the genomes of a termite and a locust to our understanding of insect neuropeptides and neurohormones - Veenstra, Jan A. (Frontiers in Physiology, 2014)
The genomes of the migratory locust Locusta migratoria and the termite Zootermopsis nevadensis were mined for genes encoding neuropeptides, neurohormones and their G-protein coupled receptors (GPCRs). Both species have retained a larger number of neuropeptide and neuropeptide GPCRs than the better known holometabolous insect species, while other genes that in holometabolous species appear to have a single transcript produce two different precursors in the locust, the termite or both. Thus the recently discovered CNMa neuropeptide gene has two transcripts predicted to produce two structurally different CNMa peptides in the termite, while the locust produces two different myosuppressin peptides in the same fashion. Both these species also have a calcitonin gene, which is different from the gene encoding the calcitonin-like insect diuretic hormone. This gene produces two types of calcitonins, calcitonins A and B. It is also present in Lepidoptera and Coleoptera and some Diptera, but absent from mosquitoes and Drosophila. However, in holometabolous insect species, only the B transcript is produced. Their putative receptors were also identified. In contrast, Locusta has a highly unusual gene that codes for a salivation stimulatory peptide. The Locusta genes for neuroparsin and vasopressin are particularly interesting. The neuroparsin gene produces five different transcripts, of which only one codes for the neurohormone identified from the corpora cardiaca. The other four transcripts code for neuroparsin-like proteins, which lack four amino acid residues, and that for that reason we called neoneuroparsins. The number of transcripts for the neoneuroparsins is about two hundred times larger than the number of neuroparsin transcripts. The first exon and the putative promoter of the vasopressin genes, of which there are about seven copies in the genome, is very well conserved, but the remainder of these genes is not. The relevance of these findings is discussed.